MANAJEMEN SUPERVISI TEMAN SEJAWAT DALAM MENINGKATKAN KINERJA GURU PADA MA NU BANAT KUDUS - Abdul Hadi Hadi; Barowi Barowi; Moh Nasuka; Munasir Munasir (PASCASARJANA UNISNU, 2019)
Abstract Purpose of this research is to know planning, implementation, evaluation, and factors which influence peer supervision in improving teacher’s performance on MA NU Banat Kudus. This research is field research by using qualitative approach. The techniques of data collection are observation, interview, and documentation. Then data is analyzed through three steps, data reduction, data presentation, and drawing conclusion or verification. Results of this research are: 1) Planning of peer supervision program held systematically by involving all of school parts. 2) Implementation of peer supervision includes before instructional stage, instructional stage, and evaluation stage. 3) Evaluation of peer supervision includes component of learning evaluation which is summative evaluation, formative evaluation, reporting result of analysis, and remedial program. 4) There are five factors which influence peer supervision in improving teacher performance at MA NU Banat Kudus which are harmonic relation, analysis of needs, strategy and media, evaluation, and revision.Keywords: Teacher Performance; management; peer supervision